2018
DOI: 10.1007/s42452-018-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and dielectric properties of sodium alginate/titanium dioxide composite membranes

Abstract: Sodium alginate/titanium dioxide solid polymer composite membranes were prepared by solution casting method. The electrical, optical and thermal properties of these composite membranes are in great demand for advanced electronic device applications. The present study is aimed at the preparation of dioxide membranes to enhance the conductivity of sodium alginate. The diffraction pattern confirmed the change of sodium alginate polymer matrix structure from amorphous to polycrystalline upon dispersing TiO 2 powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Similar observations were observed in the literature [46]. In addition, the exchange of electrons can be become very high at high frequencies [43,44].…”
Section: Dielectric Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…Similar observations were observed in the literature [46]. In addition, the exchange of electrons can be become very high at high frequencies [43,44].…”
Section: Dielectric Propertiessupporting
confidence: 90%
“…8 that the ac-conductivity was almost constant up to log f = 3. This can be observed as a result of weak response of the charge carriers at smaller frequencies [43][44][45][46][47]. However, at high frequencies, i.e., above log f = 3, a sharp increasing trend of ac-conductivity was noticed.…”
Section: Dielectric Propertiesmentioning
confidence: 97%
“…Particularly, the shape of grains almost seemed to be like stones [28]. Nanocomposite showed new interwoven structure acting as conductive pathway and leading to high conductivity as compared to that of pure NaAlg [29].…”
Section: Sem Morphologymentioning
confidence: 98%
“…Other investigated applications of the sodium alginate-TiO 2 hybrid composite include the separation process, dye-sensitized solar cell, and molecular electronics [30,69,70]. Premakshi et al [30] used a cross-linked SA-based membrane with TiO 2 for dehydration of isopropanol by pervaporation.…”
Section: Other Applications Of Sodium Alginate-tio 2 Hybrid Materialsmentioning
confidence: 99%
“…Furthermore, the hybrid composite showed improved mechanical and optical properties compared to a pure sodium alginate film in a dose-dependent manner, which was associated with the hydrogen-bond formation between both components and the increase in the π-conjugated system. Likewise, Padma et al [70] prepared an SA-based membrane reinforced with TiO 2 nanoparticles for molecular electronics applications and found that the membrane-forming solution showed improved dielectric properties and ac-electrical conductivity with better thermal stability (250 • C) than the sodium alginate membrane (180 • C).…”
Section: Other Applications Of Sodium Alginate-tio 2 Hybrid Materialsmentioning
confidence: 99%